2017
DOI: 10.1080/07315724.2017.1342576
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alpinia galanga on Mental Alertness and Sustained Attention With or Without Caffeine: A Randomized Placebo-Controlled Study

Abstract: A galanga (E-AG-01) induces a beneficial effect in mental alertness and the combination of A galanga with caffeine impedes the caffeine crash and improves sustained attention at 3 hours. Thus, these stimulant effects might yield a new usage for A galanga as a key ingredient in energy drinks or similar products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…These results are in line with prior studies that have examined the effect of adaptogens on human performance [26,28,[62][63][64]. If the study had been conducted for a longer period of time (i.e., 2.5-3 h post consumption) and the trend in improvements in cognitive task performance, vigor, and mental energy continued we may have noted a similar trend in enhanced alertness and mental energy as that recently reported by Srivastava and colleagues who also compared several treatments including a caffeinated comparator, an herbal preparation, and the herbal preparation containing caffeine and noted similar multifactorial interactions on measures of mental alertness and sustained attention [65].…”
Section: E+ Shot Vs Active Comparatorsupporting
confidence: 86%
“…These results are in line with prior studies that have examined the effect of adaptogens on human performance [26,28,[62][63][64]. If the study had been conducted for a longer period of time (i.e., 2.5-3 h post consumption) and the trend in improvements in cognitive task performance, vigor, and mental energy continued we may have noted a similar trend in enhanced alertness and mental energy as that recently reported by Srivastava and colleagues who also compared several treatments including a caffeinated comparator, an herbal preparation, and the herbal preparation containing caffeine and noted similar multifactorial interactions on measures of mental alertness and sustained attention [65].…”
Section: E+ Shot Vs Active Comparatorsupporting
confidence: 86%
“…When combined, EnXtra + caffeine did not impact the error rate as significantly as stand-alones (decrease of 7.9% [1 hour] and 8.6% [3 hours], with an increase of 6.6% by 5 hours); however, the combination remained effective in averting the caffeine crash, in a similar way as that demonstrated by the previous published study. 3 Figure 2 summarizes the percentage change in error rate from baseline.…”
Section: Discussionmentioning
confidence: 99%
“…The nootropic effect of A. galanga has also been well explored; 2 however, EnXtra, a proprietary extract of A. galanga (E-AG-01), has been proven in a clinical study to be an efficient psychostimulant. 3 In this randomized, placebo-controlled crossover study, effect of EnXtra on the attention network was studied using Fan et al's attention-network test (ANT). 4 The ANT is a widely used tool in psychophysiology to understand attention processes (alerting, orienting, and executing effects).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the reported neuroprotective [23] and the CNS stimulant [24] activities of A. galanga, Enovate Biolife explored the potentials of different extract for psychostimulant action via a pilot study [8]. The aqueous extract of A. galanga was found to be the most efficient in enhancing the mental alertness which was further assessed by a well-designed clinical study in the human population [9]. The findings indicated that the current extract central nervous system activity [25].…”
Section: Discussionmentioning
confidence: 99%
“…The extract marketed as EnXtra ® has been clinically proven to improve the mental alertness [8] [9]. The current research was conducted by Enovate Biolife, to discover the mechanism of potential nootropic compounds through their interaction with various targets (Dopamine and Acetylcholinesterase) involved in psychoactive functions.…”
Section: Introductionmentioning
confidence: 99%